2017
DOI: 10.1038/nn.4587
|View full text |Cite
|
Sign up to set email alerts
|

A common haplotype lowers PU.1 expression in myeloid cells and delays onset of Alzheimer's disease

Abstract: A genome-wide survival analysis of 14,406 Alzheimer’s disease (AD) cases and 25,849 controls identified eight previously reported AD risk loci and fourteen novel loci associated with age at onset. LD score regression of 220 cell types implicated regulation of myeloid gene expression in AD risk. In particular, the minor allele of rs1057233 (G), within the previously reported CELF1 AD risk locus, showed association with delayed AD onset and lower expression of SPI1 in monocytes and macrophages. SPI1 encodes PU.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
322
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 337 publications
(351 citation statements)
references
References 83 publications
21
322
1
Order By: Relevance
“…GRN can adopt multiple subcellular localizations from lysosomes (as granulin) to the extracellular space (as progranulin) and exerts a negative control upon microglial activation in mouse models (see Fig 5; Martens et al, 2012). Interestingly, all of the prioritized AD risk genes are Spi1 targets, substantiating the pivotal role of this transcription factor in the observed Ab-induced transcriptional response (Gjoneska et al, 2015;Huang et al, 2017). The single microglia sequencing data demonstrate that 8 of the 18 prioritized genes are more highly expressed in homeostatic microglia (HM) than in activated microglia (ARM).…”
Section: Discussionmentioning
confidence: 67%
“…GRN can adopt multiple subcellular localizations from lysosomes (as granulin) to the extracellular space (as progranulin) and exerts a negative control upon microglial activation in mouse models (see Fig 5; Martens et al, 2012). Interestingly, all of the prioritized AD risk genes are Spi1 targets, substantiating the pivotal role of this transcription factor in the observed Ab-induced transcriptional response (Gjoneska et al, 2015;Huang et al, 2017). The single microglia sequencing data demonstrate that 8 of the 18 prioritized genes are more highly expressed in homeostatic microglia (HM) than in activated microglia (ARM).…”
Section: Discussionmentioning
confidence: 67%
“…5). Of interest, rs2071305 (but not rs11039131) was in LD with rs1057233 ( r 2 = 0.65, D ′ = 0.99), a SNP that has been associated with AD age of onset in a survival analysis [20]. Collectively, these results suggest several different AD-associated genetic variants within chromosome 11.…”
Section: Resultsmentioning
confidence: 96%
“…We identified rs2071305 and rs11039131 that were tagging variants within MYBPC3 and DDB2 , within the MTCH2 and SPI1 regions. Furthermore, rs2071305 was in LD with an AD age of onset SNP that was associated with lower expression of SPI1 in monocytes and macrophages [20, 22]. We found that SPI1 expression was altered in AD brains.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, PU.1 is a pioneer transcription factor with DNA methylation sensitive binding (Stephens and Poon, 2016) critical for microglia progenitor development (Kierdorf et al, 2013; Goldmann et al, 2016), regulates microglia specific enhancers (Gosselin et al, 2014) and gene expression (Satoh et al, 2014). PU.1 and shows increased expression in human ASD brain(Gupta et al, 2014), and manipulations of PU.1 alter the expression of key microglial genes and phagocytosis function (Huang et al, 2017), indicating that changes in PU.1 binding could dramatically alter microglial function in ASD. Future studies will be needed to examine the impact of MAA on microglia from different stages of development and in altering the transcriptional response to secondary immune activation (i.e.…”
Section: Discussionmentioning
confidence: 99%